Numerical study of the effect of geometry on the behaviour of internally heated melt pools for in-vessel melt retention. (February 2023) - Venkateshwaran, Akash; Kumar, Mahendhar; M.B., Shyam Kumar; D., Davidson Jebaseelan; R., Sivakumar; Joshi, Aniket; Pain, Christopher
Abstract: In-vessel melt retention is a vital safety design that is incorporated in some nuclear reactors to protect against beyond-design basis accidents. This entails the retention of the molten fuel, colloquially known as corium, to be retained within the reactor pressure vessel (RPV) for extended periods of time without any release of radioactivity to the surroundings. Multiple experiments have been done to better understand this phenomenon, such as the COPRA experiment, which is simulated in this study. The study aims to analyse the COPRA experiment's forced convection cooling (via water) while also simulating cooling via natural convection. After comparing this to the original COPRA experiment's data, the study showcases the effect of geometry variation in such experiments by testing different RPV geometry sizes. Our results can better inform the design of future severe accident experiments while taking into account the historical aspects of severe accident research, as the popularity of Small Modular Reactors (SMRs) increases. Our analysis of the variation in geometry provides insights for RPVs that are significantly smaller than the traditional pressurised water reactors' RPV size. The difference in cooling effect and crust formation is presented for this variation of vessel size. The difference is not significant but is noteworthy for the design of future experiments and reactors.